Residual pulmonary vascular obstruction and recurrence after acute pulmonary embolism: protocol for a systematic review and meta-analysis of individual participant data. Issue 11 (28th November 2018) - Robin, Philippe; Eddy, Maggie; Sikora, Lindsey; Le Roux, Pierre-Yves; Carrier, Marc; Couturaud, Francis; Planquette, Benjamin; Pesavento, Raffaele; Rodger, Marc; Salaun, Pierre-Yves; Le Gal, Grégoire
Abstract : Background: In patients with a first, unprovoked venous thromboembolism (VTE), the optimal duration of anticoagulant therapy (AT) is controversial due to tightly balanced risks and benefits of indefinite anticoagulation. The objective of this study is to assess among patients with a first acute pulmonary embolism (PE) who received ≥3 months of AT and thereafter had a planar lung scan, whether residual pulmonary vascular obstruction (RPVO) is associated with VTE recurrence after discontinuation of AT. Methods and analysis: We will conduct a systematic review with a meta-analysis of individual participant data of contemporary studies evaluating the prognostic significance of RPVO in patients with a first acute PE. We will search from inception to 24 January 2018, PubMed, Medline, Embase and Cochrane's Central Registry for Randomized Controlled Trials, CENTRAL for randomized controlled trials and prospective cohort studies. Two reviewers will conduct all screening and data collection independently. The methodological quality and risk of bias of eligible studies will be carefully and rigorously assessed using the Risk Of Bias In Non-randomised Studies of Interventions tool. The primary objective will be to assess the relationship between RPVO on ventilation–perfusion scan after completion of at least 3 months of AT after an acute PE event, and the risk of an objectively confirmed symptomatic recurrent VTE (including deep vein thrombosis or PE) or death due to PE. The secondary objectives will include the assessment of the optimal RPVO cut-off and the risk of recurrent VTE, as well as the relationship between the relative change in RPVO between PE diagnosis and at discontinuation of AT (≥3 months) and risk of recurrent VTE. Ethics and dissemination: This study of secondary data does not require ethics approval. It will be presented internationally and published in the peer-reviewed literature. PROSPERO registration number: CRD42017081080.